The Effect of Operating Cash Flow and Sales Growth on Stock Prices of Consumer Goods Companies Listed on the Indonesia Stock Exchange in 2019-2023 - Naomi; Siti Aisyah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to assess how Operating Cash Flow and Sales Growth impact Stock Prices within consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research employs an associative method with a quantitative design. The entire group includes 74 consumer goods companies that are listed on the IDX. Using purposive sampling, the study selected a sample of 41 companies, resulting in 205 total observations during the study's timeline. The data underwent analysis using classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination), all facilitated by SPSS software. The findings indicate that Operating Cash Flow significantly and positively influences stock prices. While Sales Growth shows a positive effect on stock prices, it is not statistically significant. Together, Operating Cash Flow and Sales Growth have a noteworthy and favorable impact.